Capacity development in food and nutrition in central and Eastern Europe: A decade of achievements. (October 2020) - Gurinovic, Mirjana; Milesevic, Jelena; Zekovic, Milica; Kadvan, Agnes; Ranic, Maria; Glibetic, Maria
Highlights: NCDNCEE/CAPNUTRA initiates and supports public nutrition research CD activities. The CD process and activities have been shaped around nutrition challenges in CEE/BC. Development of nutritional research tools and food composition database. Creation of dietary intake assessment tool – Diet Assess and Plan (DAP) platform. Regionally harmonized methodology in food consumption and dietary intake assessment. Abstract: This article summarizes the activities performed by the Network for Capacity Development in Nutrition in Central and Eastern Europe and Balkan countries (NCDNCEE) in the past decade. The article gives a retrospective of the achievements and challenges in building capacity in nutrition research. Recognizing the lack of capacity and incoherent nutritional situation in CEE/BC, the United Nations University (UNU), Food & Nutrition Programme and the UN Standing Committee on Nutrition (SCN) encouraged the formation of NCDNCEE in 2005, which became CAPNUTRA in 2012. The network's aim was to initiate and support tailor-made activities for capacity development in food & nutrition in research and training in CEE/BC. To identify the challenges and needs of nutrition research in the region, the network performed inventories on existence of food composition databases, food systems elements, dietary surveys, micronutrient recommendations, application of dietary assessment methods and grey literature. Further on, the network focused on the development of food composition databases and concomitant data management software, the Diet Assess & Plan platform for food consumption collection, dietary intake assessment and nutrition planning. These and other elements form the Balkan Food Platform, which underpins harmonized nutrition research in CEE/BC. Among key actions promoted by the platform are EFSA-supported dietary surveys conducted in four Balkan countries, on children and adults, in which food consumption data are collected and analysed in a harmonized way. Cooperation with FAO and active participation in international research projects enhanced the exchange of information and knowledge and brought international recognition to the CAPNUTRA network.